2017
DOI: 10.1111/jbg.12287
|View full text |Cite
|
Sign up to set email alerts
|

Genomic estimation of additive and dominance effects and impact of accounting for dominance on accuracy of genomic evaluation in sheep populations

Abstract: The objectives of this study were to estimate the additive and dominance variance component of several weight and ultrasound scanned body composition traits in purebred and combined cross-bred sheep populations based on single nucleotide polymorphism (SNP) marker genotypes and then to investigate the effect of fitting additive and dominance effects on accuracy of genomic evaluation. Additive and dominance variance components were estimated in a mixed model equation based on "average information restricted maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
(50 reference statements)
2
14
1
Order By: Relevance
“…Ratios of dominance deviation variance for traits related to carcass composition ranged from null to moderate to low values (0.14 and 0.12 for BFT in PB and CB, respectively). The ratio of dominance variance ranged from 0.00 to 0.07 across different BW and scanned body composition traits in a purebred population, and from 0.07 to 0.19 in a combined crossbred population in sheep (Moghaddar and van der Werf, 2017). This ratio decreased to 0.03 and 0.09 after accounting for heterosis effects.…”
Section: Variance Of Dominance Deviation Effectsmentioning
confidence: 93%
See 1 more Smart Citation
“…Ratios of dominance deviation variance for traits related to carcass composition ranged from null to moderate to low values (0.14 and 0.12 for BFT in PB and CB, respectively). The ratio of dominance variance ranged from 0.00 to 0.07 across different BW and scanned body composition traits in a purebred population, and from 0.07 to 0.19 in a combined crossbred population in sheep (Moghaddar and van der Werf, 2017). This ratio decreased to 0.03 and 0.09 after accounting for heterosis effects.…”
Section: Variance Of Dominance Deviation Effectsmentioning
confidence: 93%
“…Although not relevantly different, estimated dominance values for lifetime daily gain in the Piétrain population in Lopes et al (2015) are slightly higher than ours, possibly because they used a model that did not account for inbreeding. Estimates of dominance variance can be inflated when average heterozygosity or inbreeding is not accounted for in the model (Aliloo et al, 2017;Moghaddar and van der Werf, 2017). Su et al (2012) reported that dominance variance represented about 5% of the phenotypic expression of ADG in Duroc pigs.…”
Section: Variance Of Dominance Deviation Effectsmentioning
confidence: 99%
“…Genomic selection models with dominance have been tested in several populations, including dairy cattle (Ertl et al, 2014 ; Aliloo et al, 2016 ; Jiang et al, 2017 ), pigs (Esfandyari et al, 2016 ; Xiang et al, 2016 ), sheep (Moghaddar and van der Werf, 2017 ), and layers (Heidaritabar et al, 2016 ) with ambiguous results. Jiang et al ( 2017 ) found a negligible percentage of variation explained by dominance effects for productive life in a Holstein cattle population, although Ertl et al ( 2014 ) suggested that dominance may suppose up to 39% of the total genetic variation for Somatic Cell Score in a population of Fleckvieh cattle.…”
Section: Genomic Selection Models With Dominancementioning
confidence: 99%
“…However, results of this approach showed no improvement in hybrids predictions or in hybrids ranking (data not shown), although some exciting results have been reported in the literature (Dias, Gezan, Guimarães, Nazarian, et al., 2018; dos Santos, Vasconcellos, Pires, Balestre, & Von Pinho, 2016). Some bottlenecks associated with this result could be that the estimation of dominance effects requires specific mating designs (Nazarian & Gezan, 2016), and confounding between additive and nonadditive genetic components (Lee, Goddard, Visscher, & Van Der Werf, 2010; Moghaddar & van der Werf, 2017; Muñoz et al., 2014; Nazarian & Gezan, 2016). An increase in the number of evaluated hybrids could overcome this issue.…”
Section: Discussionmentioning
confidence: 99%